Author Correction: Metabolic gene expression and epigenetic effects of the ketone body β-hydroxybutyrate on H3K9ac in bovine cells, oocytes and embryos. Issue 1 (December 2018) - Sangalli, Juliano; Sampaio, Rafael; del Collado, Maite; da Silveira, Juliano; De Bem, Tiago; Perecin, Felipe; Smith, Lawrence; Meirelles, Flávio
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.